The Regulatory Effects of Long Noncoding RNA-ANCR on Dental Tissue-Derived Stem Cells - Qian Jia; Xiaolin Chen; Wenkai Jiang; Wei Wang; Bin Guo; Longxing Ni (Stem Cells International)
Long noncoding RNAs (lncRNA) have been recognized as important regulators in diverse biological processes, such as transcriptional regulation, stem cell proliferation, and differentiation. Previous study has demonstrated that lncRNA-ANCR (antidifferentiation ncRNA) plays a key role in regulating the proliferation and osteogenic differentiation of periodontal ligament stem cells (PDLSCs). However, little is known about the role of ANCR in regulating other types of dental tissue-derived stem cells (DTSCs) behaviours (including proliferation and multiple-potential of differentiation). In this study, we investigated the regulatory effects of lncRNA-ANCR on the proliferation and differentiation (including osteogenic, adipogenic, and neurogenic differentiation) of DTSCs, including dental pulp stem cells (DPSCs), PDLSCs, and stem cells from the apical papilla (SCAP) by downregulation of lncRNA-ANCR. We found that downregulation of ANCR exerted little effect on proliferation of DPSCs and SCAP but promoted the osteogenic, adipogenic, and neurogenic differentiation of DTSCs. These data provide an insight into the regulatory effects of long noncoding RNA-ANCR on DTSCs and indicate that ANCR is a very important regulatory factor in stem cell differentiation.